Redefining Professional Competence in the Era of Artificial Intelligence: The Strategic Importance of Soft Skills and Emotional Intelligence - Ramadhan, Akbar Fadhl; Ferdinand , Evan (International Journal Administration, Business & Organization, 2026)
The rapid advancement of Artificial Intelligence (AI) and digital technologies has transformed the landscape of professional competence in the modern workforce. This study explores how the integration of AI influences the redefinition of professional skills, emphasizing the growing importance of soft skills and emotional intelligence alongside technical expertise. Through a comprehensive literature review, this research examines recent developments from 2020 to 2025 to identify patterns in how digital transformation reshapes individual and organizational performance. The findings reveal that while automation and data-driven systems enhance operational efficiency, they also create new demands for adaptability, empathy, and collaborative communication. Technical proficiency alone is no longer sufficient to ensure professional success; workers must possess hybrid competencies that combine digital literacy with emotional and social awareness. Emotional intelligence, in particular, strengthens employees’ capacity to manage stress, maintain ethical decision-making, and foster innovation within teams. Furthermore, the study highlights the strategic role of educational institutions in integrating soft skills and emotional development into curricula to prepare graduates for global competition. The implications suggest that balanced professional development merging technological capability with emotional intelligence is key to thriving in the rapidly evolving digital economy.